Correlating genotype with phenotype using CFTR‐mediated whole‐cell Cl− currents in human nasal epithelial cells. (8th December 2021) - Noel, Sabrina; Servel, Nathalie; Hatton, Aurélie; Golec, Anita; Rodrat, Mayuree; Ng, Demi R. S.; Li, Hongyu; Pranke, Iwona; Hinzpeter, Alexandre; Edelman, Aleksander; Sheppard, David N.; Sermet‐Gaudelus, Isabelle
Abstract : Abstract: Dysfunction of the epithelial anion channel cystic fibrosis transmembrane conductance regulator (CFTR) causes a wide spectrum of disease, including cystic fibrosis (CF) and CFTR‐related diseases (CFTR‐RDs). Here, we investigate genotype–phenotype–CFTR function relationships using human nasal epithelial (hNE) cells from a small cohort of non‐CF subjects and individuals with CF and CFTR‐RDs and genotypes associated with either residual or minimal CFTR function using electrophysiological techniques. Collected hNE cells were either studied directly with the whole‐cell patch‐clamp technique or grown as primary cultures at an air–liquid interface after conditional reprogramming. The properties of cAMP‐activated whole‐cell Cl − currents in freshly isolated hNE cells identified them as CFTR‐mediated. Their magnitude varied between hNE cells from individuals within the same genotype and decreased in the rank order: non‐CF > CFTR residual function > CFTR minimal function. CFTR‐mediated whole‐cell Cl − currents in hNE cells isolated from fully differentiated primary cultures were identical to those in freshly isolated hNE cells in both magnitude and behaviour, demonstrating that conditional reprogramming culture is without effect on CFTR expression and function. For the cohort of subjects studied, CFTR‐mediated whole‐cell Cl − currents in hNE cells correlated well with CFTR‐mediated transepithelial Cl − currents measured in vitro with the Ussing chamber technique, but not with those determined in vivo with the nasal potential difference assay. Nevertheless, they did correlate with the sweat Cl − concentration of study subjects. Thus, this study highlights the complexity of genotype–phenotype–CFTR function relationships, but emphasises the value of conditionally reprogrammed hNE cells in CFTR research and therapeutic testing. Key points: The genetic disease cystic fibrosis is caused by pathogenic variants in the cystic fibrosis transmembrane conductance regulator (CFTR), an ion channel, which controls anion flow across epithelia lining ducts and tubes in the body. This study investigated CFTR function in nasal epithelial cells from people with cystic fibrosis and CFTR variants with a range of disease severity. CFTR function varied widely in nasal epithelial cells depending on the identity of CFTR variants, but was unaffected by conditional reprogramming culture, a cell culture technique used to grow large numbers of patient‐derived cells. Assessment of CFTR function in vitro in nasal epithelial cells and epithelia, and in vivo in the nasal epithelium and sweat gland highlights the complexity of genotype–phenotype–CFTR function relationships. Abstract : Abstract figure legend This study investigated cystic fibrosis transmembrane conductance regulator (CFTR) function in human nasal epithelial (hNE) cells. Using the whole‐cell patch‐clamp technique, the properties and magnitude of CFTR Cl − currents in hNE cells isolated from fully differentiated primary cultures after conditional reprogramming culture were identical to those of freshly isolated hNE cells. These results demonstrate that conditional reprogramming culture is without effect on CFTR expression and function.